Work addiction - the result of “weak will” or the need for perfection? - Atroszko, Paweł (Studia Psychologica: Theoria et praxis, 2010)
According to the existing studies the important predictors of the levels of work addiction are action control (Atroszko, 2009; Wojdyło i Lewandowska-Walter, 2009) and the neurotic perfectionism (Atroszko, 2009). On the basis of the literaturę of the subject there were formulated hypotheses stating that dysfunctional perfectionism dimensions: concem over mistakes and doubts about actions mediate the link between action control and workaholism. Baron and Kenny’s (1986) approach was used to verify the mediation hypotheses. As predicted both concem over mistakes and doubts about actions are mediating variables between action control subseąuent to failure and work addiction. Similarly both dimensions of the neurotic perfectionism mediate the link between decision related State orientation and workaholism.